Elementary Mathematics Teachers' Knowledge of Equity Pedagogy - Christa Jackson (Arizona State University, 2013)
Currently, mathematics instruction in U.S. classrooms is far from achieving equity for African American students. This qualitative study reports the results of eight successful elementary mathematics teachers knowledge of equity pedagogy, specifically their knowledge of culturally relevant pedagogy, cultural competence, and critical consciousness. Teachers knowledge of equity pedagogy was examined using interview data. The results of this study revealed that successful mathematics teachers of African American students have knowledge of equity pedagogy. Implications for teacher preparation and professional development programs are discussed.